(untitled) (PANGEEA, 2025)
Coaching is one of the well-known educational methods used nowadays in developing soft skills, social skills and managerial skills. The last research shows that, after the IT industry, the coaching activities are the second more explosively developed and profitable field in the world. The question that raised from this is: What is happening in our society that cause this acute need of developing new skills? The 21st Century brought so many changes for society, institutions and organizations which are now looking actively for new and efficient educational methods that can help people to develop new skills and adapt more easily to change. Coaching became the best solution for many organizations when it comes to adapting to changes. This paper explores the changes that have occurred in the last years worldwide and presents a case study about this famous educational method called coaching. What is coaching and what makes this educational method to be chosen in times of change? One of the answers may consist in the versatility to be used face to face, online, by phone, one to one or in groups and the advantage of providing at the same time a feeling of support, guidance, knowledge, trust, motivation and empowerment. Using coaching as an educational method promotes a new pattern of communication in organizations and helps obtaining ownership, resilience and proactivity when facing changes. Skills as ownership, resilience and proactivity are one of the most desirable abilities when it comes to changes and are not easy to develop with habitual educational methods. Coaching, an educational method borrowed from sport and used in organizations mainly in the last 50 years, brings us the hope in obtaining the skills we need to face the changes that are coming to the world.